2019
DOI: 10.1111/ijfs.14346
|View full text |Cite
|
Sign up to set email alerts
|

Use of culled goat meat in frankfurter production – effect on sensory quality and technological properties

Abstract: Summary Four different levels (25–100%) of culled goat meat were used in frankfurter formulation (frankfurters G25, G50, G75 and G100) instead of beef (CON). Technological properties, fatty acid profile and sensory properties were examined during the 6‐week cold storage. The formulation had significant impact of fatty acids profile – n‐6/n‐3 ratios progressively decrease from 14.63 in CON to 6.63 in G100. Higher goat meat content led to progressively higher lightness and lower redness in frankfurters. This was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(37 citation statements)
references
References 41 publications
(72 reference statements)
1
36
0
Order By: Relevance
“…To soothe the goat flavor, making a more acceptable product to consumers, the authors suggested replacing goat fat with beef fat. The sensory quality of culled goat meat frankfurters [13] showed very close grades between the goat and beef (CON) frankfurters, and no significant differences were noticed for odor, taste, hardness and juiciness. Color was the single attribute significantly different in frankfurter formulations.…”
Section: Sensory Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…To soothe the goat flavor, making a more acceptable product to consumers, the authors suggested replacing goat fat with beef fat. The sensory quality of culled goat meat frankfurters [13] showed very close grades between the goat and beef (CON) frankfurters, and no significant differences were noticed for odor, taste, hardness and juiciness. Color was the single attribute significantly different in frankfurter formulations.…”
Section: Sensory Qualitymentioning
confidence: 99%
“…In a study, meats of sheep and goats from culled animals were pointed out as valuable alternatives to that meat-producing sausages with different levels of pork fat [9]. The nutritional characteristics and consumer acceptability of different combinations of goat meat with beef have been studied [42], and the technological properties in frankfurter productions were studied using meat from culled animals [13].…”
Section: Sausagesmentioning
confidence: 99%
See 1 more Smart Citation
“…During storage, a slight increment of pH values was observed (up to 0.09), signifi cantly only in CONF and ALGF, but without an infl uence on the relations within treatments. Though signifi cant differences were found, the pH values of all model system emulsions, on day 0 and throughout storage, were within the range for the emulsifi ed-type of sausages made of beef [Vural & Javidipour, 2002], pork/beef [Yotsuyanagi et al, 2016], and goat/beef [Stajić et al, 2020].…”
Section: Changes Of Ph Valuesmentioning
confidence: 99%
“…However, this did not lead to different relations between treatments. An increase in cohesiveness during storage was observed in emulsifi edtype meat products with different formulations [Pintado et al, 2016b;Salcedo-Sandoval et al, 2013;Stajić et al, 2020].…”
Section: Texture Propertiesmentioning
confidence: 99%